Relationship of Nurse Motivation with The Implementation of Physical Examination of Patients - Muhammad Irwan; Aco Mursid; Risnah; Rosmah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2021)
Physical examination is one of the efforts to handle health to clients. Physical examination is carried out on the patient's body by means of inspection, palpation, percussion, and auscultation to find out any changes in physiological function in the body. If the physical examination is not done by the nurse in doing nursing care, then the nursing diagnosis he sets will be wrong, and will actually cause new problems in patients. Of course, there are things that are the cause why a nurse does not do a physical examination, so research needs to be done to find the reason. The design used in this study is cross-sectional studies. The results of the study were obtained with questioner and observation sheets on 58 respondents, namely 26 nurses in Cempaka inpatient rooms and 32 nurses in dahlia inpatient rooms, knowing the relationship of motivation.